Loss-of-function mutants and overexpression lines of the Arabidopsis cyclin CYCA1;2/Tardy Asynchronous Meiosis exhibit different defects in prophase-i meiocytes but produce the same meiotic products. - Yixing Wang; Ming Yang (PLoS ONE, 2014)
In Arabidopsis, loss-of-function mutations in the A-type cyclin CYCA1;2/Tardy Asynchronous Meiosis (TAM) gene lead to the production of abnormal meiotic products including triads and dyads. Here we report that overexpression of TAM by the ASK1:TAM transgene also led to the production of triads and dyads in meiosis, as well as shriveled seeds, in a dominant fashion. However, the partial loss-of-function mutant tam-1, an ASK1:TAM line, and the wild type differed in dynamic changes in chromosome thread thickness from zygotene to diplotene. We also found that the pericentromeric heterochromatin regions in male meiocytes in tam-1 and tam-2 (a null allele) frequently formed a tight cluster at the pachytene and diplotene stages, in contrast to the infrequent occurrences of such clusters in the wild type and the ASK1:TAM line. Immunolocalization studies of the chromosome axial component ASY1 revealed that ASY1 was highly expressed at the appropriate male meiotic stages but not localized to the chromosomes in tam-2. The level of ASY1, however, was greatly reduced in another ASK1:TAM line with much overexpressed TAM. Our results indicate that the reduction and increase in the activity of TAM differentially affect chromosomal morphology and the action of ASY1 in prophase I. Based on these results, we propose that either the different meiotic defects or a common defect such as missing ASY1 on the chromosomal axes triggers a hitherto uncharacterized cell cycle checkpoint in the male meiocytes in the tam mutants and ASK1:TAM lines, leading to the production of the same abnormal meiotic products.